2000
DOI: 10.1046/j.1442-9993.2000.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting potential impacts of environmental flows on weedy riparian vegetation of the Hawkesbury–Nepean River, south‐eastern Australia

Abstract: Remnants of native riparian vegetation on the floodplain of the Hawkesbury–Nepean River near Sydney, have significant conservation value, but contain a large component of weeds (i.e. exotic species that have become naturalized). A proposal for the introduction of environmental flows required an assessment of potential impacts on 242 native and 128 exotic species recorded along 215 km of the river. The likely effects of frequency, season, depth and duration of inundation were considered in relation to habitat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…It can be combined with vegetation map, because the vegetation species are affected by the inundation frequency and depth (Shafroth et al 1998;Wassen et al 2003;Ward et al 2013;Howell and Benson 2000), and its results are shown in Fig. 6.…”
Section: Results and Discussion: Hydrological Regime Using Ieps And Vmentioning
confidence: 99%
“…It can be combined with vegetation map, because the vegetation species are affected by the inundation frequency and depth (Shafroth et al 1998;Wassen et al 2003;Ward et al 2013;Howell and Benson 2000), and its results are shown in Fig. 6.…”
Section: Results and Discussion: Hydrological Regime Using Ieps And Vmentioning
confidence: 99%
“…The replacement of natives with exotics in wetlands leads to changes in the quality of organic matter entering the wetland, and often to changes in the timing of organic matter processing (Schulze and Walker 1997). Aquatic weeds are relatively uncommon in rain-filled wetlands because of their isolation from waterways, which can carry propagules downstream (Howell and Benson 2000). Terrestrial weeds, however, are a common feature of rain-filled wetlands during the dry phase.…”
Section: Weedsmentioning
confidence: 99%
“…Several studies reported increased frequencies of exotic species in response to increased disturbances at the level of river dynamics such as channel disturbances through sedimentation, stream current exposure, and flood frequency (Pabst andSpies 1998, Zimmerman et al 1999), of human activities (Tabacchi 1995), and of nutrient levels (Howell and Benson 2000). The high percentage of weeds along the river has substantial implications for conservation efforts.…”
Section: -19mentioning
confidence: 99%
“…In many instances the characterization of species as weeds, pioneer species, annuals and/or perennials, and exotic species have been used to assess vegetation patterns in relation to specific physical environmental gradients (Howell and Benson 2000;Tabacchi 1995;Zimmerman et al 1999). Several studies reported increased frequencies of exotic species in response to increased disturbances at the level of river dynamics such as channel disturbances through sedimentation, stream current exposure, and flood frequency (Pabst andSpies 1998, Zimmerman et al 1999), of human activities (Tabacchi 1995), and of nutrient levels (Howell and Benson 2000).…”
Section: -19mentioning
confidence: 99%